Exploring English self-concept and investment of successful EFL learners from a Chinese secondary school - Hengjie Chen; Dingfang Shu (Studies in Second Language Learning and Teaching, 2024)
Academic self-concept, a central psychological construct that powerfully explains learners’ varied motivations and learning behaviors, needs to be further explored to deepen our understanding of language learner psychology. Drawing on self-reported learning histories, this study investigates the English self-concept of successful English as a foreign language (EFL) learners and their mediated learning behaviors from the theoretical lens of personal investment theory (Maehr & Braskamp, 1986). Data were collected from 12 students at a key secondary school in Shanghai using retrospective narratives and semi-structured interviews. The analysis revealed three categories of cognitive and affective characteristics in the learners’ English self-concept and the corresponding investment features with subtle differences identified. Participants espoused average to high competency beliefs and moderate to strong positive affect toward English learning, nurtured by positive self-beliefs such as interest and self-efficacy formed through early English learning experience. Their sustainable, targeted, and resilient investment in English learning was also underpinned by the perception of mastery and performance goals appropriately afforded by teachers, parents, peers, or the school. Practical implications for parents and educators are discussed in terms of what they can do to help learners build positive self-perceptions as EFL learners.